Factors Affecting Adherence to Antiretroviral Treatment in Harari National Regional State, Eastern Ethiopia. (29th August 2013) - Mitiku, Habtamu; Abdosh, Tekabe; Teklemariam, Zelalem
Abstract : Background . The efficacy of antiretroviral treatment (ART) depends on strict adherence to the regimen, but many factors have been identified for nonadherence. Method . To identify the factors for non-adherence to ART, a cross-sectional study was conducted on people living with human immunodeficiency virus (HIV) and attending the ART service at Hiwot Fana and Jugal hospitals; it was done from October to December, 2010. Adherence was defined as taking 95% of the prescribed doses in the week before the survey. Data were collected using a standard interview questionnaire and were analyzed using SPSS Version 16. Result . Among the 239 study participants, the magnitude of adherence to ART in the week before interview was 87%. The main reasons for nonadherence were forgetting (47.2%), traveling (18.9%), and being busy doing other things (15.1%). There was not any independent predicator identified for adherence to ART. Conclusion . Compared to other similar studies in Ethiopia, in this study a high adherence rate was found. Forgetfulness was the most common reason for the nonadherence. Therefore, the ART counseling needs to give emphasis to using memory aids. In addition, a further study on adherence rate and its determinants with multiple adherence measurements is recommended.